NGO IN INTERNATIONAL COOPERATION: SOUTH SOUTH COOPERATION IN SUB SAHARAN AFRICA. - ESEMU MARLICK LEKUIPI (Graduate School of International Studies Ajou University, 2020)
ABSTRACT Over the years we have experienced several variations to the world system dating back from precolonial era, colonial and post-colonial era which one can say are very defining moments in world history in and these various eras greatly defines today. With the emergence of an “unstoppable” globalization which is aimed at drawing the world closer into a global village we are left to ponder on the question, how is globalization going to impact the course of the world judging from the premise that there exists already a world system of classification wherein it is already difficult as it is for one nation to move from one class to another bet for a few miraculous examples like South Korea, Singapore. Globalization in all its generalization has brought some strengths as well as weaknesses which can be better drafted to define the feature of an emerging global world. All these would mean taking a much more inclusive approach in an attempt to include all stakeholders and to match various groups to developmental projects that best suit their need rather than the previous approach believing that there is a “one-work-for all” approach that can be simply developed and transplanted in various areas of the world which again over the years have proven to be futile. This new approach to development has brought in many actors separate from the state and multinational to include others in the likes of civil societies as well as NGOs which have taken the lead role in redefining what and how international cooperation can better impact a more community based society.
학위논문(석사)--Graduate School of International Studies Ajou University :NGO학과,2020. 2
Keywords: IDC; International Development Coorperation